Pengaturan Keterbukaan Pelaksanaan Persidangan Arbitrase (Studi Perbandingan Antara Indonesia Dan Singapura) - Yusuf Arifin; Titania Titania; Imam Hakiki (Journal Law and Government, 2025)
Arbitration proceedings are conducted in private and confidential, a principle that is universally accepted in arbitration practice around the world. The private nature of arbitration proceedings ensures the confidentiality of the parties' disputes, given that arbitration is a forum for resolving business disputes where the evidentiary process often requires parties to present evidence in the form of business contracts containing company secrets. There are a number of countries that regulate the conduct of arbitration proceedings in an absolute closed manner, such as Indonesia. However, some countries, such as Singapore, regulate the conduct of arbitration proceedings in a non-absolute closed manner. Singapore's regulations allow for arbitration proceedings to be open in certain circumstances. Arbitration proceedings may be open if the parties to the dispute agree to open them. The arbitral tribunal may order arbitration proceedings to be open in disputes involving the public interest. Conducting arbitration proceedings in the open can provide legal protection for the public and fulfill the right to social control over an arbitration dispute involving the public interest. The concept of regulating open arbitration proceedings can be applied in Indonesia to disputes involving the public interest, such as arbitration disputes involving the government, local governments, state-owned company, and regional-owned company (known as BUMN and BUMD).